2019
DOI: 10.1111/pde.14054
|View full text |Cite
|
Sign up to set email alerts
|

Purpuric nail striae as the initial manifestation in multisystem Langerhans cell histiocytosis

Abstract: Nail involvement in Langerhans cell histiocytosis (LCH) is very uncommon. We describe a 9‐month‐old boy with longitudinal purpuric bands, onychodystrophy, and paronychias on his fingernails and toenails, which antedated manifestations of recurrent bilateral spontaneous pneumothorax and elevated transaminases. The diagnosis of nail LCH was then confirmed by immunohistochemistry demonstrating positive S100 and CD1a staining in the epithelium of nail bed tissue. This case report affirms that nail involvement may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…The significance of nail involvement in patient prognosis is controversial. Although it is associated with multi-system involvement and poor prognosis, some studies have reported that patients with nail involvement show favorable prognoses, as in this case 3 4 . Therefore, whether nail change constitutes an independent indicator for prognosis remains to be elucidated.…”
mentioning
confidence: 66%
“…The significance of nail involvement in patient prognosis is controversial. Although it is associated with multi-system involvement and poor prognosis, some studies have reported that patients with nail involvement show favorable prognoses, as in this case 3 4 . Therefore, whether nail change constitutes an independent indicator for prognosis remains to be elucidated.…”
mentioning
confidence: 66%
“…8 Among all the organs, LCH occurring in vulvar and nail was extremely rare for children, its dermoscopic and RCM features had been less investigated, meanwhile, nail LCH (NLCH) and vulvar LCH (VLCH) indicated the herald symptom of underlying multisystem disease. 11,12 We retrieved the papers in the fields of LCH, dermoscopy, and RCM from the NCBI, Web of Science, and Google of database, the dermatoscopic and RCM features of VLCH have less been investigated. We found that the clinical characteristics of children VLCH and/or N LCH (presented onycholysis and purpuric striae 13 ) were different from those of adults and other anatomic locations and were also prone misdiagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Among all the organs, LCH occurring in vulvar and nail was extremely rare for children, its dermoscopic and RCM features had been less investigated, meanwhile, nail LCH (NLCH) and vulvar LCH (VLCH) indicated the herald symptom of underlying multisystem disease 11,12 . We retrieved the papers in the fields of LCH, dermoscopy, and RCM from the NCBI, Web of Science, and Google of database, the dermatoscopic and RCM features of VLCH have less been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…et al (2020) describe a 9-month-old boy with longitudinal stripes, onychodystrophy and paronychia on the nail plates of the hands and feet. Nail damage was the initial manifestation of multisystem Langerhans cell histiocytosis [14]. G. Moreno-Coutiño et al (2016) in their study consider the occurrence of onychodystrophy in elderly patients as a possible marker of peripheral artery disease, being an important factor in early diagnosis [15].…”
Section: Introductionmentioning
confidence: 99%